Retracted Research: The effect of employing computerized clouds to develop creative thinking among tenth grade students in computer science Irbid Governorate - Amaireh, Mohammad AbdAlHleem (Journal of Educational and Psychological Sciences, 2022)
*This research was retracted on July 24, 2023The study aimed at recognizing the effect of cloud computing method (represented by the Google Drive application) on developing tenth grade creative thinking at the computer school subject. The study used the semi-experimental approach. The forty subjects study sample were selected by using the intentional method and divided into 20 unit for both of the experimental and control groups. It was found that using the cloud computing method in teaching, positively affects the tenth graders' creative thinking with its three domains (fluency, originality, and flexibility) and its development. There is significant statistical difference at the ratio of(a 0.05) in the creative thinking scale prepared by the researcher (proved creditable and constant) for the experimental group attributed to the cloud computing teaching method compared to the control group taught by conventional method.For these results the researcher recommend to use cloud computing in all different courses in school.
Keywords: Cloud Computing; Development of creative thinking; Computer subject